Basic embolization techniques: tips and tricks - Ierardi, Anna Maria; Piacentino, Filippo; Pesapane, Filippo; Carnevale, Aldo; Curti, Marco; Fontana, Federico; Venturini, Massimo; Pinto, Antonio; Gentili, Francesco; Guerrini, Susanna; De Filippo, Massimo; Giganti, Melchiore; et al. (Acta Biomedica Atenei Parmensis, 2020)
Good knowledge of the various approaches of embolization of peripheral bleedings and different embolic materials available is of paramount importance for successful and safe embolization. We review and illustrate the main endovascular and percutaneous techniques used for embolization, along with the characteristics of the different embolic materials, and the potential complications.